Автоматизация контроля статуса гидратации пациента во время процедуры гемодиализа - Ткачук, Богдан Владимирович (НТУ "ХПИ", 2016)
В данной статье описана проблема оценки водного статуса пациентов на гемодиализе. Показана важность обретения пациентом состояния нормогидратации или "сухого веса" и опасность при его отсутствии. Разработана структура системы для контроля статуса гидратации, описана функциональная схема, устройство и принцип работы ее блоков. Разработан алгоритм работы системы, основанный на физико-биологических процессах происходящих в организме пациента при ультрафильтрации. Выполнено компьютерное моделирование подтверждающее адекватность разработанного алгоритма.

In this article the problem of assessing the water status of patients on hemodialysis described. The importance of obtaining a patient’s condition normohydratation or "dry weight" is shown. Also, the risk of lack of "dry weight" in patients with kidney disease is described. The purpose of the development of the system has to monitor the patient’s hydration status, based on a mathematical model describing the processes in the body fluid during hemodialysis procedure. Also automated algorithm ultrafiltration removing liquid should be developed. The structure of the system to monitor hydration status is developed. Hemodialysis machine, apparatus bioimpedancemeter and to determine the "dry weight" make up this system. The block diagram shows a commercially available bioimpedance. Furthermore, the apparatus and the principle of their operation are described. The algorithm of the system based on the physical and biological processes occurring in the body of the patient with ultrafiltration built. Hematocrit is the main factor of the state of the vascular fluid selected. Expression hematocrit calculation of the variable component of bioimpedance found. Separation of all time on dialysis three stages proposed. Also control the rate of removal of excess fluid vascular and interstitial fluid during hemodialysis offered. Computer modeling of the new algorithm is satisfied. Adequacy is shown. The need for further experimental studies of the system and algorithm specified.
Automation control status hydration of patients during hemodialysis
Keywords: биоимпеданс; гипергидратация; ультрафильтрация; искусственная почка; bioimpedance; hyperhydration; ultrafiltration